PENYELESAIAN SENGKETA ATAS HAK PENGELOLAAN TANAH WADUK ANTAR GAMPONG SECARA ADAT DI KECAMATAN TRING GADENG PIDIE JAYA - nur aini; Herinawati H; Muhibuddin M (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2022)
Abstrac The settlement of disputes related to reservoir land management rights located in Tring Gadeng District involved the communities of Gampong Meunasah Dee and Gampong Pulo fighting each other for management rights to reservoir land, giving rise to disputes that must be resolved based on customary settlements in Aceh. This is in accordance with Aceh Qanun Number 9 of 2008 concerning the Guidance of Indigenous Life and Customs. In this qanun, it has been explained that each customary dispute resolution in Aceh must first be resolved with existing regulations, both at the village level and at the city level. The research method in this thesis uses empirical juridical research with the type of qualitative research, and the nature of the research is descriptive analysis. The research location is located in Tring Gadeng District, Pidie Jaya, the population used is related to efforts to resolve disputes over land management rights between gampongs traditionally in Tring Gadeng district, Pidie Jaya. The results showed that the settlement of disputes over the customary management rights of inter-gampong reservoirs in Tring Gadeng District, Pidie Jaya was carried out by customary deliberation (mediation) which was resolved by the two gampong officials, Mukim Peuduk Tunong, Camat Tring Gadeng and supervised by the Tring Gadeng Police Chief. The obstacle experienced in this research is that the Gampong Pulo community complicates the dispute resolution process so that it becomes complicated, and the dispute resolution process is slow. Efforts to resolve these obstacles are carried out by peaceful deliberation and approaches to parties who insist on demanding reservoir land management rights. The conclusion in this study is that dispute resolution between gampongs is resolved by customary deliberation (mediation) by carrying out the stages of meetings and approaching parties who demand management rights. courts, and the community must also always be able to accept dispute resolution by customary deliberation according to the decision of the Mukim, Camat and Kapolsek Tring Gadeng as parties participating in the dispute resolution process. Keywords: Dispute Resolution, Land, Management Right